Stress and burnout as determinants of teachers' under- performance in private secondary schools in Ibadan metropolis, Oyo state (2021)
Teaching is becoming more challenging as a profession and is one of the most significant and visible professions in the world. This study looked at stress and burnout as predictors of teachers' under-performance in private secondary schools in Ibadan, Oyo State. The study used descriptive survey research with the target population consisting of randomly chosen teachers in Ibadan city. A purposive sampling technique was employed to pick 150 respondents from 15 selected private schools and a research instrument titled "Stress, Burnout and Teachers' Performance Questionnaire" (SBTPQ) was utilised to collect data far the study. According to the findings, stress is a predictor of teachers' effectiveness, (r = .516. n= 150, p < .05) and burnout is a predictor of teachers' performance, (r=610, n=I50 p<.05). Based on these findings, it was suggested that social workers should push for work stress audits far teachers at regular intervals in order to identify work stress regions. Schools could also arrange lectures and workshops on holistic work-life balance far teachers.